Superplasticity : common basis for an ubiquitous phenomenon /: common basis for an ubiquitous phenomenon. (2018) - Padmanabhan, K. A (Kuppuswamy Anantha), 1945-; Prabu, S. Balasivanandha; Mulyukov, Radik R; Nazarov, Ayrat; Imayev, R. M; Chowdhury, S. Ghosh
No abstract available